Maximum voltage gain index for distributed generators based on voltage power system profile - S.Jaber, Aqeel (International Journal of Engineering and Technology, 2019)
The challenges facing power systems have shown a growing tendency in the studies on distributed generation in the modernized world. One of the most important objectives of distributed generation systems is an improvement of the quality of power systems. Many indices have been proposed in the electrical power system literature. However, the previous criteria did not give a clear voltage advantage of the distributed generatorâ€™s location. In this paper, a new index is proposed to gauge the placement of distributed generators (DGs) in a power system. The new index depends on the maximum voltage gain (MVG) in the system to overcome the position of the DG. The Gauss-Seidel load flow method is used to test the voltages of IEEE 30-bus standard after and before adding of DGs. The results show that MVG is more feasible than other indices such as cumulative voltage deviation (CVD) and voltage stability index (VSI) for calculating suitable locations for DGs. Â